Rancang bangun pabrik pengolahan kulit kelinci menjadi kulit kelinci berbulu samak krom skala kecil - Harniniek Harniniek; Titik Purwati Widowati (Majalah Kulit, Karet, dan Plastik, 1988)
This paper is prepared for a design of a small scale chorme tanning factory, processing fur rabbit leather. The capacity of it will be 200 pieces/day green rabbit skin.  This factory will be profitable in the view of techno – economical calculations are as follows : the total capital is fixed capital + working capital = Rp 49.276.532,00 the total production cost is variable cost for a year + fixed cost for a year = Rp. 41.241.203,76 variable cost for a  year consists of raw material, packing, chemical/supplement material electricity, fixed cost of a year consists of labour salaries, capital interest, maintenance, depreciation and general expences; the manufacturing cost is the total  production divided by production  capacity = Rp. 700,85 / sq. ft; the profit calculation before taxing is Rp. 14.682.636,24, after taxing id Rp. 11.746.108,99; the pay out period calculation consists of the percentage of profit to return the capital (rate of return) before taxing is 29,80 %, 3 years, after taxing 3 years 8 months; the break even point calculations is the break even point is the Rp. 28.768.403,47 the percentage of break even point is 51,44 % and the capacity of break even point is 30.281,29 sq. ft. NBThe price of calculations above at the 1987.